A atenção secundária à saúde na pandemia da COVID-19 em Minas Gerais: uma análise empírica da resposta do SUS no enfrentamento dos casos graves - Sousa, Josimary Conceição de (2023)
In an unprecedented and unexpected crisis situation like the COVID-19 pandemic, the sudden increase in acute health cases arising from an unknown disease further exacerbates the problems caused by limited resources dedicated to public health services. In the case of Brazil, the challenge has been even greater due to its vast territorial extension, as well as the complexity of its healthcare system, structured in a federative context where the effectiveness is conditioned to its governance capacity as established constitutionally. In a historical context of regional inequalities, the microregional coverage capacity in the management of severe cases depends on the configuration of regionalization of healthcare networks in each state, which is influenced by structural heterogeneities [availability of physical, human, and financial resources], governance capacity [capacity of governance in the collegiate instances of discussion and decision-making], as well as socioeconomic and demographic differences [social determinants of health] among the different microregions of the state. Therefore, the aim of this research was to investigate the responsiveness of the Unified Health System (SUS) in the state of Minas Gerais in addressing severe cases of COVID-19, specifically with regard to medium-complexity hospital services. Using a quantitative methodological approach based on the Performance Evaluation Dimensions Matrix of the Health System The results demonstrated that the system responded with an increase in financial investments and an equitable increase in bed capacity, directing more beds to microregions that had a higher number of deaths. Furthermore, the healthcare structure showed improved performance with an increase in beds in microregions with higher resolvability, which positively impacted health conditions by reducing the number of deaths.